(untitled) (PERENNIAL, 2023)
Preservation is one way to extend the life of shallow, quality wood. However, synthetic chemical preservatives, especially those made from CCA (Copper, Chrom, Arsenic), are dangerous for the environment because they are difficult to decompose and can also cause health problems for humans. Utilization of natural preservatives from plant extracts is one effort to reduce this. Plants that have the potential as natural preservatives are Lannea coromandelica (Javanese wood). Java wood contains compounds in the form of flavonoids, saponins, polyphenols and tannins, which can inhibit the growth of Candida albicans and Trichophyton mentagrophytes fungi. This study aims to determine the effectiveness of Lannea coromandelica bark and stem extract at concentrations of 25 ppm, 50 ppm, 75 ppm and 100 ppm on the growth of the mycelium of the wood rot fungus Schizophyllum commune. The study was conducted by mixing the extracts of each concentration in the growth media and then inoculating the wood rot fungus S. commune right in the middle of the growth media. The research data were analyzed using a split-plot design and analyzed using a split-plot design with two factorial split plots. Two factorial split-plot analyses showed that the concentration change treatment significantly affected the growth of the S. commune mycelium. The results showed that the effectiveness of Java bark extract at all concentrations was classified as very resistant with an Antifungal Activity (AFA) value of 100%, and Java bark extract at a concentration of 25 ppm showed effectiveness that was classified as resistant with an AFA value of 71%). The concentration of the extract affects the growth of the S. commune mycelium. The higher the concentration, the slower the growth of the S. commune mycelium occurs. Java bark extract with a concentration of 25 ppm and 50 ppm has the potential to be a natural wood preservative because it can reduce the growth of the mycelium of the wood rot fungus S. commune.